PREVALENCE AND IMPACT OF CYBERBULLYING IN A SAMPLE OF INDONESIAN - Dinada Masrufah; Lorenza Indah (DUTA BANGSA UNIVERSITY INDONESIA, 2021)
In recent years cyberbullying has become widespread throughout junior high schools around the world, resulting in high numbers of adolescents affected by cybervictimization. Cybervictimization is associated with negative psychological health outcomes. The objective of the present study was to examine the impact and prevalence of cybervictimization in a sample of junior high school students in Jogjakarta, Indonesia. A total of 102 seventh grade students were involved in the study: 72 (70.6%) boys and 30 (29.4%) girls. The majority (80%) of the students in this study reported experiencing cybervictimization occasionally to almost every day. The results suggest a positive relationship between cybervictimization and level of students' psychological distress. General recommendations for anti cyberbullying programmes are discussed.